Desenvolvimento de aplicativo para auxílio na prevenção de acidentes com máquinas agrícolas - Frederico, Liah Donato (2023)
Operations involving agricultural machinery in Brazil's rural areas have predominantly been associated with a significant proportion of serious accidents. As technology advances and more sophisticated equipment is implemented, the risks inherent in these operations also increase proportionally. In order to develop an effective mechanism to provide indispensable guidance to reduce these alarming rates, this project aims to develop an application for mobile devices, compatible with the Android and IOS operating systems. The software was programmed using the Dart programming language and followed the agile Scrum methodology in its development process. The application stands out for its intuitive keys and dynamic interfaces, with Regulatory Standard No. 31 (NR-31), which establishes guidelines for good safety practices at work when operating machinery, being the guideline for the content presented. The built-in tabs explore not only relevant information, but also action tools that contribute to worker safety. This app, in addition to its effective functionality, represents a significant integration between technology and the dissemination of knowledge. By offering practical education using accessible language, the app aims in the long term to have a positive impact on reducing the risks faced by agricultural machinery operators, resulting in a minimization of fatalities and exposure to occupational hazards.